Family businesses: A literature review from an agency perspective (2010)
This article presents a comprehensive review of the financial literature consisting of the main studies on family businesses. Focusing on the agency theory*the review describes the main agency problems that arise between managers and owners*between managers and debt holders*and between majority and minority shareholders in a family ownership structure. Three decades of family business articles published in the main financial journals are reviewed. This look at the literature on the topic evidences a field of research that is incipient*little explored in Latin America*for which empirical comparison and contrasting is necessary in order to understand the family ownership structure worldwide. The article ends by proposing a family business research agenda including topics such as financial performance*the role of the heirs*debt structure*the composition of the board of directors*the impact of agency costs on capital costs*and private control benefits.